Dealing with water scarcity in the next century - Rosegrant, Mark W. (International Food Policy Research Institute, 1995)
Reform of water policy is urgently needed to avert severe national, regional, and local water scarcities that will depress agricultural production and worsen water-related health problems. Water is abundant globally but scarce locally. Countries are considered water scarce when annual internal renewable water resources are less than 1,000 cubic meters per capita per year. Below this threshold, water availability is considered a severe constraint on socioeconomic development and environmental quality. Currently, some 30 countries are considered water stressed, of which 20 are absolutely water scarce. By 2020, the number of water scarce countries will likely approach 35. Equally worrisome, virtually all developing countries, even those with adequate water in the aggregate, suffer from debilitating seasonal and regional shortages that urgently need to be addressed. Cooperation between countries sharing the same water basin will become increasingly important as water becomes scarcer. Reconciliation is cheaper than armed conflict. A key to defusing potential international conflicts over water is national water policy reform to ensure the most efficient use of available water supplies. Countries must therefore begin the painful process of reforming national water policies and treating water as a scarce resource.